Respuesta :

Answer:

[tex]x=-24[/tex]

Step-by-step explanation:

[tex]\frac{x}{12} +\frac{1}{3} =-\frac{5}{3}[/tex][tex]=\frac{x}{12}[/tex]

Subtract 1/3 from both sides;

[tex]\frac{x}{12} +\frac{1}{3} -\frac{1}{3} =-\frac{5}{3}-\frac{1}{3}[/tex]

Simplify;

[tex]\frac{x}{12} +\frac{1}{3} -\frac{1}{3} =-\frac{5}{3}-\frac{1}{3}[/tex]

Simplify;

[tex]\frac{x}{12} +\frac{1}{3} -\frac{1}{3}[/tex]

Add similar elements;[tex]\frac{1}{3} -\frac{1}{3} =0[/tex]

[tex]=\frac{x}{12}[/tex]

Simplify; [tex]-\frac{5}{3} -\frac{1}{3}[/tex]

=[tex]\frac{-5-1}{3}[/tex]

Subtract the numbers;-5-1=-6

[tex]\frac{-6}{3}[/tex]

Apply fraction rule;

[tex]-\frac{6}{3}[/tex]

Divide the numbers [tex]\frac{6}{3}[/tex]

=-2

[tex]\frac{x}{12} =-2[/tex]

Multiply both sides by 12

[tex]\frac{12x}{12} =12(-2)[/tex]

Simplify;

[tex]x=-24[/tex]

ACCESS MORE